1998
DOI: 10.1021/ja9734004
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of 1-(1-Alkynyl)cyclopropanols to 2-Cyclopentenones via Their Hexacarbonyldicobalt Complexes. A New Use of Alkyne−Co2(CO)6 Complexes in Organic Synthesis

Abstract: A novel rearrangement of 1-(1-alkynyl)cyclopropanols to 2-cyclopenten-1-ones proceeded on complexation of their alkynyl part with octacarbonyldicobalt (Co 2 (CO 8 )). 1-(1-Alkynyl)cyclopropanols with a wide range of substituents on their alkyne terminus rearranged to the corresponding 3-substituted 2-cyclopenten-1-ones in good yield. In case of the reactions of 1-alkynylcyclopropanols with an alkyl substituent on the cyclopropane ring, either 4-substituted or 5-substituted 2-cyclopenten-1-ones could be selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Treating 1‐alkynyl cyclopropanol 116 with stoichiometric quantities of cobalt delivers cyclopentenone 117 (Scheme a). Later, by adding a triarylphosphite ligand to the reaction, the cobalt loading could be reduced to 5–10 mol‐% without affecting product yields . Trost and co‐workers have shown that a ruthenium catalyst is also competent in this reaction …”
Section: Homoenolates As Nucleophilic Reagentsmentioning
confidence: 99%
“…Treating 1‐alkynyl cyclopropanol 116 with stoichiometric quantities of cobalt delivers cyclopentenone 117 (Scheme a). Later, by adding a triarylphosphite ligand to the reaction, the cobalt loading could be reduced to 5–10 mol‐% without affecting product yields . Trost and co‐workers have shown that a ruthenium catalyst is also competent in this reaction …”
Section: Homoenolates As Nucleophilic Reagentsmentioning
confidence: 99%
“…Comparison of the coupling constants with known data15 and additional NOE experiments confirmed that the hydrogen atoms are trans-positioned in compound 10 and cis-positioned in compound 11.…”
mentioning
confidence: 60%
“…Various alkynyl substituents containing a functional group can also be employed in this reaction as shown in Table 1. 7 In case of transformation of alkynylcyclopropanols with a substituent on the 2-position of the cyclopropane ring, two regioisomers, that is, the 4-substituted and/or 5-substituted 2-cyclopentenones can be formed, depending on which bond of the cyclopropane is cleaved (Scheme 5). Firstly the reaction of (1R*, 2S*)-2-methyl-1-phenylethynylcyclopropanol 6a cis (R=Ph, R 1 =Me, R 2 =R 3 =H) was examined according to the aforementioned procedure.…”
Section: Methodsmentioning
confidence: 99%